2013
DOI: 10.4236/eng.2013.52019
|View full text |Cite
|
Sign up to set email alerts
|

Building Failure Causes in Nigeria and Mitigating Roles by Engineering Regulation and Monitoring

Abstract: This paper assessed some of the reported cases of building failures and their possible causes in Nigeria between 1977 and 2011. The reported major failure causes are structural failure (SF), Carelessness (CLSS), poor workmanship (PW), poor supervision (PS), poor materials (PM), and quackery (Q).These causes of failure were subjected to Chi-Square statistical test at 5% significant level and 4 degree of freedom to know the most common cause of failure in Nigeria. The analysis showed quackery as the principal cu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 0 publications
1
5
0
Order By: Relevance
“…In the opinion of this researcher, life imprisonment may still not solve the problem of non-compliance, instead adequate machinery and the engagement of relevant stakeholders should be encouraged in finding lasting solutions to the problem. This study agreed with other relevant stakeholders who suggested legislative enactment of the BC, monitoring and evaluation of building development projects by professional bodies, empowerment of enforcement agencies, the introduction of an independent regulatory body, the insurance of building projects, the introduction of forensic analysis to aid in assessing the actual causes of failure, skills training, and continuous professional development (Ayedun et al, 2012;Dahiru et al, 2012;Olagunju et al, 2013;Tanko et al, 2013).…”
Section: Potential Solutions To the Problemsupporting
confidence: 83%
See 1 more Smart Citation
“…In the opinion of this researcher, life imprisonment may still not solve the problem of non-compliance, instead adequate machinery and the engagement of relevant stakeholders should be encouraged in finding lasting solutions to the problem. This study agreed with other relevant stakeholders who suggested legislative enactment of the BC, monitoring and evaluation of building development projects by professional bodies, empowerment of enforcement agencies, the introduction of an independent regulatory body, the insurance of building projects, the introduction of forensic analysis to aid in assessing the actual causes of failure, skills training, and continuous professional development (Ayedun et al, 2012;Dahiru et al, 2012;Olagunju et al, 2013;Tanko et al, 2013).…”
Section: Potential Solutions To the Problemsupporting
confidence: 83%
“…For example, Olaitan and Yakubu (2013) observed regulatory enforcement failure and non-compliance with the BC in Nigeria after assessing 167 building projects, only 28 of which (16%) had obtained approval, only 10 of which utilised the services of at least one professional (0.59%), and none of which were subject to recorded site visits, indicating a total failure of (Tanko et al, 2013, citing Ayedun et al, 2012Bayo, 1995;Olagunju et al, 2013;Windapo and Rotimi, 2012, all cited in Yakubu and Agapiou, 2016). Fagbenle and Oluwunmi (2010) argued that these failures were the result of professionals and non-professionals undermining the regulation of the BC for structural building development projects due to inadequate legislation and a lack of accountability within the industry.…”
Section: Evidence Of Non-compliance With Building Standards and Regulmentioning
confidence: 99%
“…In the bid to achieve home ownership as cheaply as possible, some low-income developers employ quacks at the design and construction phases of their development which leads to the erection of collapse-vulnerable buildings [28,20]. Fakere, Fadairo, and Fakere, [29] and Adewole, Oladejo, and Ajagbe, [30] for instance, showed that buildings under construction can collapse as a result of poor concrete mix ratio due to inadequate supervision by the consultants [11,13,22,23]. Clearly, building projects for which there are no consultants, and those being supervised by quacks will be worse of.…”
Section: Collapse Of Old Buildings and Buildingsmentioning
confidence: 99%
“…Oloyede et al [11] and Hassan et al [21] attributed the causes of building failure to faulty construction methodology, which results from the engagement of unqualified personnel. The use of quacks has been top of the list on the factors causing building collapse [20][21][22][23]27]. Some authors believe that poor workmanship is a key factor contributing to building collapse in Nigeria [20,22,32,33].…”
Section: Construction-related Causes Of Buildingmentioning
confidence: 99%
See 1 more Smart Citation